Profil zabójcy w "Julu" Pawła Goźlińskiego = The profile of a killer in Paul Goźliński's "Jul" - Libera, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paris, summer 1845. The city is shocked by an extremely sophisticated act of murder; the policeimmediately suspects Polish immigrants, who are unpopular in the capital for their brawls, theirpermanent conflicts with the law, political conspiracy and suspicious religious activity. InspectorLang, however, is forced to use the services of a Polish spy, who is involved in the crime.
Keywords: Goźliński, Paweł (1971- ); powieść kryminalna; literatura polska - 21 w. - tematyka